GENERALIZED SCHWINGER DUALITY IN BOUND-STATE THEORY - CHHAJLANY, SC (Amer Inst Physics, 1993)
It is shown that an exactly solvable bound state problem is the generator of a nonterminable sequence of partially exactly solvable problems. The reversible passage from exact to partial solvability is realized through a class of admissible nonlinear coordinate transformations of which the parabolic Schwinger transformation that relates the Coulomb and oscillator problems is a particular case. Interesting spectral features of a novel set of partially solvable problems that emerge through the present considerations are also pointed out.
Keywords: Exactly-Solvable Potentials; Schrodinger-Equation; Anharmonic-Oscillators; Algebra